Complications and reoperations after laparoscopic radical cystectomy in a Japanese multicenter cohort. (1st February 2019) - Kanno, Toru; Ito, Katsuhiro; Sawada, Atsuro; Saito, Ryoich; Kobayashi, Takashi; Yamada, Hitoshi; Inoue, Takahiro; Ogawa, Osamu
Abstract : Objectives: To describe the complications and their surgical management after laparoscopic radical cystectomy in a Japanese multicenter cohort. Methods: The participants were drawn from a retrospective multicenter study at 10 institutions. We identified 436 patients who underwent laparoscopic radical cystectomy with no robot assistance. Early and late complications were graded according to their Clavien–Dindo classification. The records of all patients who underwent surgical interventions for laparoscopic radical cystectomy‐specific complications were also reviewed. Kaplan–Meier curves were used to describe the time to surgical intervention. Results: The 90‐day rates for overall complications, high‐grade complications (Clavien–Dindo classification III–V) and mortality were 53%, 17% and 1.4%, respectively. Gastrointestinal (25%), infectious (22%) and abdominal wall‐related (9%) complications were the most common. The late complication rate was 18%, and a total of 81 patients (19%) underwent surgical intervention during the median follow‐up period of 22 months. The reoperation rate was 25% at 5 years. Gastrointestinal complications in the early postoperative period and abdominal wall‐related complications in the late postoperative period were the main reasons for reoperation. Seven (7%) out of 100 female patients underwent emergent surgical reoperation for transvaginal bowel evisceration as a result of vaginal dehiscence. Conclusions: Early and late postoperative complications and surgical reoperations are notable after laparoscopic radical cystectomy. Abdominal wall‐related complications including vaginal dehiscence are common, and they represent the main indication for reoperation during long‐term follow up.